Der hl. Franz Xaver und das Krebswunder - Grabner, Elfriede (Traditiones (Ljubljana), 1999)
Aside from songs and catechesis employed in the course of their missionary work the jesuits also used pictures and effective motifs on altar paintings and chuch frescoes. The author analyzes how the motif of the Jesuit saint Francis Xavier's miracle within the crab spread through legens, school and prayer books and graphics, but also with the help of paintings in churches anddchapels, thus enchancing the worship of his saint
Keywords: Franciscus Xaverius, sanctus, 1506-1552; cerkveno slikarstvo; ikonologija; svetniki; češčenje; motivi